STRATEGI PEMASARAN DAN PENINGKATAN KUALITAS KERIPIK SUKUN - Noer Novijanto; Eka Ruriani; Fahrudin TK (JURNAL AGROTEKNOLOGI, 2011)
The marketing of bread fruit chips in UD. Jamila Jamur Sukses was still not good, therefore the company has to develop its strategy by improving the quality of bread fruit chips to increase the marketing sales. This research was intended to analyse internal and external factors affecting UD. Jamila Jamur Sukses. The method used was SWOT analysis followed by FMEA analysis to know the fsctors affecting quality. The internal factors involved strength and weakness, and the external factors involved opportunity and threats. Results showed that from the SWOT analysis it was known that the position of the company in cell IV. It means that the company is in the condition of stability . Subsequently, the FMEA analysis showed that the failure of quality involves harder,rancid, and packaging, off flavor were often happen. Keywords: marketing strategy, quality improvement, SWOT and FMEA analysis